Breastfeeding initiation rates among immigrant women in central Italy between 2006 and 2011. (17th January 2016) - Farchi, Sara; Asole, Simona; Chapin, Elise M.; Di Lallo, Domenico
Abstract: Objective : This study was aimed at evaluating differences in breastfeeding initiation rates by maternal place of birth among women giving birth in one of 14 hospitals in Lazio, Italy, between 2006 and 2011. Methods : The data on 14 hospitals for this study were taken from a survey on healthy newborns carried out during the month of October each year. It collected information on maternal characteristics and infant feeding during the hospital stay. The exposure variable was maternal place of birth. The outcome variable was infant feeding during hospital stay classified as exclusive breastfeeding, predominant breastfeeding (PBF), complementary feeding or formula feeding. Both a descriptive analysis and a logistic regression on infant feeding (exclusive/PBF versus partial or non-breastfeeding) by maternal place of birth were carried out. The logistic regression model was adjusted for confounding factors. A random effect model was used to take into account the correlation of data among the hospitals. Results : Among the 6505 mothers included in this study, 18.7% were born in non-industrialized countries. Overall, 64.9% of mothers exclusively breastfed their babies, with lower prevalence among Asiatic mothers. The logistic model confirmed that breastfeeding was lower among infants born to Asian mothers (OR: 0.52; 95% CI: 0.35–0.77) compared with other groups, taking into account the effect of the other variables included in this model. Intracluster correlation was equal to 26%, showing that the hospital's model of care is a strong predictor of the initiation of breastfeeding. Conclusions : These data are useful for targeting disadvantaged groups when promoting breastfeeding.